2019
DOI: 10.1002/jpen.1591
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐Based Strategies and Recommendations for Preservation of Central Venous Access in Children

Abstract: Children with chronic illness often require prolonged or repeated venous access. They remain at high risk for venous catheter–related complications (high‐risk patients), which largely derive from elective decisions during catheter insertion and continuing care. These complications result in progressive loss of the venous capital (patent and compliant venous pathways) necessary for delivery of life‐preserving therapies. A nonstandardized, episodic, isolated approach to venous care in these high‐need, high‐cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 170 publications
0
38
0
6
Order By: Relevance
“…In this study, nonadherent cases seem to be associated with a prolonged length of stay, which can increase several risks related to the hospital setting, costs for the healthcare system, and the psychological suffering of children [3,21]. However, a prolonged duration of hospitalization may also be affected by other factors not considered in this analysis, such as the severity of the disease.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In this study, nonadherent cases seem to be associated with a prolonged length of stay, which can increase several risks related to the hospital setting, costs for the healthcare system, and the psychological suffering of children [3,21]. However, a prolonged duration of hospitalization may also be affected by other factors not considered in this analysis, such as the severity of the disease.…”
Section: Discussionmentioning
confidence: 78%
“…Several associations have defined appropriateness criteria and guidelines in VAD management [7,[17][18][19][20]. Baskin et al [21] suggested a multidisciplinary approach to venous access care in patients with chronic VAD insertion. In their recommendation, venous access planning should begin at first diagnosis, defining the need for acute or chronic use (Grade C, Class IIa).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] An additional 9 articles comprising organizational guidelines, consensus, recommendation, and position papers included separately as important papers to our practice. [13][14][15][16][17][18][19][20][21] Of these 15 finalist articles, 6 were published in Journal of Parenteral and Enteral Nutrition, 6 in Clinical Nutrition, 2 in Journal of Trauma and Acute Care Surgery, and 1 in Nutrition in Clinical Practice. Individual rankings, based on relevancy to pharmacy nutrition support clinical practice according to the author participant group, are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Baskin et al 13 Evidence-based strategies and recommendations for preservation of central venous access in children Bugaev et al 14 Promotility agents for the treatment of ileus in adult surgical patients: A practice management guideline from the Eastern Association for the Surgery of Trauma Bugaev et al 15 Antimotility agents for the treatment of acute noninfectious diarrhea in critically ill patients: A practice management guideline from the Eastern Association for the Surgery of Trauma Jensen et al 16 GLIM criteria for the diagnosis of malnutrition: A consensus report from the Global Clinical Nutrition Community Kovacevich et al 17 American Society for Parenteral and Enteral Nutrition guidelines for the selection and care of central venous access devices for adult home parenteral nutrition administration Mogensen et al 18 Academy of Nutrition and Dietetics/American Society for Parenteral and Enteral nutrition consensus malnutrition characteristics: Usability and association with outcomes Plauth et al 19 ESPEN guideline on clinical nutrition in liver disease Singer et al 20 ESPEN guideline on clinical nutrition in the intensive care unit Volkert et al 21 ESPEN guideline on clinical nutrition and hydration in geriatrics .92, and 1.37 mg, respectively. The authors concluded that trace element contamination is prevalent in PN components and their findings support reformulation of adult, pediatric, and neonatal manufactured MTE products to eliminate chromium, reduce manganese (elimination in neonatal products), and supply full daily physiologic requirements of selenium, zinc, and copper.…”
Section: First Author Titlementioning
confidence: 99%
“…Some CVS classification systems have been described in other fields, such as in the evidence based strategies and recommendations for preservation of central venous access in children by Baskin et al. 21 A customized classification of CVS in hemodialysis population might be helpful to facilitate future diagnosis and treatment as well.…”
Section: Discussionmentioning
confidence: 99%